Classification of units in phraseology – a contemporary typological proposal - Sułkowska, Monika (Papers in Linguistics, 2024)
The article concerns the issue of classifying phraseological units. In the first part of the text, the author reviews various typological concepts that appeared in phraseology in the 20th and 21st century. The analysis reveals a number of changes that have occurred in phraseology over the years in line with the development of this research field. In the second part of the article, the author presents a proposal for the classification of phraseological units which correlates with the contemporary scope of phraseological research. The proposed typology includes three groups of phraseological units, such as phraseological syntagms, functional phraseological sequences and phraseological utterances. Phraseological syntagms include two subgroups, i.e. collocations and locutions, while phraseological utterances are divided into paremias and pragmatemes. Each of the groups distinguished in the proposed typology is defined, described and provided with examples in the text.